Quantification of serum HBXAP DNA in lung cancer patients by quantitative fluorescent polymerase chain reaction - Hou, Yu-Lei; Chen, Hui; Ge, Ming-Jian; Li, Feng-Zeng; Xue, Cheng-Jun; Wu, Yan-Feng; Luo, Hai-Xia (Molecular biology reports, 2013)
Hepatitis B virus x associated protein ( HBXAP ), as a subunit of chromatin remodeling and spacing factor, plays a critical role in cancer development through gene amplification. In this study, we aimed to quantify the levels of serum HBXAP DNA, to analyze and compare its diagnostic value with existing clinical parameters in lung cancer, and to potentially provide a novel tumor marker for lung cancer. Serum HBXAP DNA from 65 lung cancer patients and 20 healthy controls was quantified using real-time fluorescent quantitative polymerase chain reaction (FQ-PCR) analysis. The data were analyzed by statistical software SPSS 13.0. We found that serum HBXAP DNA levels in lung cancer patients were higher compared to healthy controls ( u = 219.0, p = 0.001) and were closely associated with TNM stage and lymph node metastasis ( p = 0.015 and p = 0.016, respectively). However, serum HBXAP DNA levels were not associated with patient age, gender, smoking status, histological type, or tumor size ( p > 0.05). We identified a sensitivity of 61.9 % and a specificity of 93.7 % for the ability of HBXAP DNA levels to detect lung cancer at a cutoff value of 1,557.6 copies/μl. The sensitivity for existing lung-tumor markers, such as squamous cell carcinoma antigen, cytokeratin fragment 21-1, and neuron specific enolase, was increased from 35.7 %, 53.5 %, and 56.0 % to 75.0 %, 86.0 %, and 80.0 %, respectively, by inclusion of serum HBXAP DNA. Taken together, quantification of serum HBXAP DNA by FQ-PCR could potentially serve as a novel complementary tool for the clinical screening and detection of lung cancer.